Measuring adherence to antiretroviral treatment and assessing factors affecting adherence in a state primary healthcare clinic, Mitchells Plain Community Health Centre - T. Engel; A. Schlemmer (South African Family Practice)
Background: A need was identified to measure adherence levels to antiretroviral treatment (ART) in a resource-poor setting and to assess the impact on adherence to ART of partner disclosure, partner support, other support, and length of time between diagnosis and ART commencement.